PEMAKNAAN PERAN MATA KULIAH AKUNTANSI SYARIAH DI PERGURUAN TINGGI DALAM PEMILIHAN KARIR DI LEMBAGA JASA KEUANGAN SYARIAH - Sutrisna S, Anna; Muchlis, Saiful (Universitas Muhammadiyah Surakarta, 2016)
This study aims to discover the role of Accounting Sharia courses in college against the interests of students accounting for a career in the Organization of Islamic Financial Services. This study is a qualitative research and processed using interpretive paradigm in the level of theory and practice. The informants as many as five people who are accounting students who have passed the course Accounting Sharia in Politeknik Negeri Ujung Pandang. The results of this study showed that purport accounting subjects of sharia in college in the selection of a career in financial services institution of sharia are students there who were trapped in material values that are infused with the scent of mechanistic and unisex students who expect professionalism tiered in a career in LJKS and neglect the suitability of theory and practice in operational performance in LJKS. Those that are still stuck in the value circle material in the sense of an income. In addition there are also prioritizing the suitability of theory and practice. But there are still caught in a cycle value of the materials in an income and interpret the meaning of the latter is to ignore the suitability of theory and practice in operational performance in LJKS and still trapped inside the circle in the value of the material interpret the meaning of an income. Overall concluded that accounting sharia courses in college for students accounting role in the selection of a career in LJKS.